Pengaruh Suhu dan Hormon Pertumbuhan Terhadap Produksi Bunga Stek Pucuk Melaleuca Alternifolia - Liliana Baskorowati (Jurnal Pemuliaan Tanaman Hutan, 2009)
Melaleuca alternifolia is the main source for Australian tea tree production. Improving oil quality has been attempted by controlled cross pollination between plus trees. The availability of flowers during flowering season is important for control pollination between , therefore the work to  stimulate flowering should be done. The objective of this study was to increase the flora bud production of 24 month cuttings of M. alternifolia by application of growth retardant (paclobutrasol) and exposure to low  temperatures. Results showed that the application of paclobutrazol was not effective to increase the number of floral buds production. Paclobutrazol application effected only some morphological characteristics. Such as reduced height, smaller leaves, and shorter internodes. On the other hand, exposure of shoot cutting to low temperature for 4 months period increased the number of floral buds and paclobutrazol application following exposure to low temperature was then assumed to have been responsible for the floral response..